Attitudes toward vaccination among healthcare workers: a cross-sectional study from Italy. (30th September 2020) - Di Martino, G; Di Giovanni, P; Cedrone, F; D'Addezio, M; Di Girolamo, A; Masciarelli, M; Meo, F; Scampoli, P; Di Sciascio, M B
Abstract: Background: In Italy, the loss of confidence in vaccines has resulted in low vaccination coverage also among healthcare workers (HCWs). Low vaccination coverage among HCWs may lead to dangerous outbreaks and may increase absenteeism. The aim of this study was to investigate vaccine coverage and the attitudes toward vaccination among HCWs. Methods: A multicenter cross-sectional study was conducted from August to November 2019 among HCWs referring to all the hospitals of the Local Health Authority 02 of Abruzzo Region, Italy. The survey was based on the questionnaire proposed by the H-ProImmune Project, aiming at investigating vaccination coverage and beliefs towards vaccination. Besides a descriptive analysis of the results, a logistic regression analysis was performed to evaluate the association between vaccine coverage and type of occupation (medical doctor, nurse, obstetric nurse, other). Results: A total of 347 HCWs were enrolled in the study. The 57.3% reported to have missed diphtheritis-tetanus-pertussis (DTP) vaccination, the 50.1% reported to have missed measles-mumps-rubella (MPR) vaccination, and the 62.5% reported to have missed flu vaccination. In comparison with medical doctors, obstetric nurses were more likely to be associated to MPR vaccination (OR 2.8;95%CI 1.1-7.6; p = 0.047). As far as flu vaccination was concerned, both nurses and obstetric nurses showed lower confidence (respectively OR 0.2; 95%CI 0.1-0.3; p < 0.001 and OR 0.1; 95%CI 0.1-0.5; p = 0.003). Moreover, other healthcare professionals reported to believe in natural immunization more than in vaccination (26.5%; p < 0.001) and they were also worried about long-term effects of vaccination (10.2%; p = 0.044). Differently, nurses were more frequently worried about vaccine side effects (24%; p < 0.001). Conclusions: This survey shows that the vaccination coverage taken into consideration results to be below the 95% threshold. Training on vaccine and mandatory measures may be necessary in order to achieve better coverage. Key messages: Among HCW all vaccination coverage considered resulted below the threshold. Training on vaccine and mandatory measures may be needed in order to achieve better coverage.